How Do College Students Perceive Their Partner Responds to Them When They Refuse Sexual Activity? - Marcantonio, Tiffany L. (Violence against women, 2025)
Refusal communication is a dyadic process, with one person communicating a refusal and another person responding. To enhance our understanding of this process, we surveyed college students to assess their interpretation of their partners’ responses when they declined vaginal–penile sexual activity. In an online survey, participants were prompted to describe their partners’ reactions when participants refused their partner's vaginal–penile sex initiation. Through content analysis, three themes were present: (1) partner accepted the refusal, (2) partner experienced negative emotions, (3) partner ignored their refusals. Participants frequently reported their refusals were accepted. Sexual assault prevention initiatives should work to normalize refusal communication.